The Recent Surge in Medical Research Journalism in Pakistan. A Boon or Bane? - Baseer, Najma (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Medical research journalism in Pakistan has lately seen a significant rise, increasing public engagement with health and science updates across the globe. Numerous causes have contributed to this notable surge, including increasing faculty productivity because of their professional and personal development and the abundance of national and international funding opportunities in medical research. As a result, Pakistani researchers now have an additional platform for publishing and disseminating their work, raising their profile, and fostering more regional and international collaborations. This is further complemented by the fact that, despite stringent indexation criteria drawn at the national level by both the Pakistan Medical and Dental Council (PMDC) and the Higher Education Commission (HEC), many universities have started their journals in anticipation of enhancing their university rankings. Owing to these academic, technological, and societal causes, Pakistan’s medical journalism industry has grown quickly, presenting opportunities and challenges. Further, a critical analysis of this phenomenon poses the question: is this surge a boon or bane for the country’s medical and scientific fraternity? This editorial will discuss both views shaping the landscape for medical journalism in Pakistan.